PERAN KOMUNITAS PENGGIAT LINGKUNGAN DALAM PENGELOLAAN SAMPAH PLASTIK DI DESA PENATIH DANGIN PURI, DENPASAR - Ni Luh Putu Ening Permini; I Dewa Gede Putra Sedana (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
This study aims to determine the role of the environmental activist community in plastic waste management and analyze the factors that support and hinder the role of the environmental activist community in managing plastic waste in Penatih Dangin Puri Village, Denpasar. This study uses a qualitative descriptive approach. The theory used is Role Theory. to analyze the role of environmental activist communities in plastic waste management and use Charles O. Jones' Implementation Theory. To analyze the factors that support and hinder the role of environmental activist communities in the management of plastic waste. The results of this study indicate that the role of the environmental activist community in managing plastic waste in Penatih Dangin Puri Village, Denpasar has not been carried out optimally, community activities are in accordance with Bali Governor Regulation No. The factors that support the role of the environmental activist community in the management of plastic waste are the participation of the community in plastic waste processing activities and good cooperation between environmental activist communities, while the inhibiting factors are limited funds in activities with the absence of government attention to community activities.